2006
DOI: 10.1038/sj.onc.1209810
|View full text |Cite
|
Sign up to set email alerts
|

RB silencing compromises the DNA damage-induced G2/M checkpoint and causes deregulated expression of the ECT2 oncogene

Abstract: As alterations in retinoblastoma (RB)/E2F pathway are commonly found in human cancers, the molecular mechanism underlying cell cycle deregulation caused by the mutations in the RB/E2F pathway needs to be investigated extensively. Compared with good understanding of RB/E2F functions in G1-S cell cycle progression, it is not fully understood how an abrogated RB pathway affects the G2-M phase of the cell cycle. Here, we report that disruption of RB accelerated G2-M progression in the presence of DNA damage by ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 41 publications
3
53
0
Order By: Relevance
“…27,28 Proper RB function is required for maintenance of G2/M arrest following DNA damage and disruption of RB accelerated G2/M progression in the presence of DNA damage by elevating E2F activity and the expression of a mitotic regulatory genes. 29 Our results demonstrated that CARF suppression led to hypophosphorylated RB and downregulation of E2F1, suggesting that CARF inhibition may also activate this pathway to bring about growth arrest. However, although Saos-2 cells, which lack RB, were resistant to CARF-inhibition induced cell death, restoration of RB to Saos-2 did not revert the phenotype, which indicated that RB is not sufficient to revert the apoptosis induced by CARF suppression.…”
Section: Cyclinsmentioning
confidence: 75%
“…27,28 Proper RB function is required for maintenance of G2/M arrest following DNA damage and disruption of RB accelerated G2/M progression in the presence of DNA damage by elevating E2F activity and the expression of a mitotic regulatory genes. 29 Our results demonstrated that CARF suppression led to hypophosphorylated RB and downregulation of E2F1, suggesting that CARF inhibition may also activate this pathway to bring about growth arrest. However, although Saos-2 cells, which lack RB, were resistant to CARF-inhibition induced cell death, restoration of RB to Saos-2 did not revert the phenotype, which indicated that RB is not sufficient to revert the apoptosis induced by CARF suppression.…”
Section: Cyclinsmentioning
confidence: 75%
“…Our results are consistent with previous studies based on combined cross-linking DNA immunoprecipitation and microarray experiments, 52 which have identified some of the same targets we have uncovered as E2F4 target genes with a putative role in various phases of the cell cycle including G 2 and M. 53 Similar targets were independently identified in studies examining specific p130 or Rb-regulated gene expression. 24 At the same time, Rb-deficient U2OS cells showed an analogous dependence on E2F4-regulated genes, 48 suggesting a context-dependence for p130 or Rb requirement for regulating mitotic entry. From our results and other studies we conclude that in response to DNA damage, these tumor Figure 3.…”
Section: E2f Family Proteins: From Dna Damage To a Stable G 2 Arrestmentioning
confidence: 94%
“…56,57 Interestingly, a number of E2F4-bound genes originally identified through array analyses were also bound by E2F1, 53 an observation extended to the promoters of genes regulated during G 2 and M containing distinct E2F4 and E2F1 binding sites. 52,58 Some of these promoters may display collaborative binding of several E2F family members to the same elements, such as in case of ect-2, 48 while others distinct positive and negative E2F-dependent regulatory elements. 58 In addition, E2F-dependent transcriptional activity may require binding of other transcription factors, such NF-Y or Myb to regulate the transcription of Cdk1.…”
Section: © 2 0 0 7 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has indicated that loss of RB function may play a role in this process; for example, by inducing defects during the replication of DNA, and potentially by causing abnormal segregation of chromosomes during mitosis (Kennedy et al 2000;Foijer et al 2005;Eguchi et al 2007). Embryonic stem cells (ESCs), which are largely devoid of a G1 checkpoint, provide a good system to investigate a potential role for the RB pathway in G2/M (Conklin and Sage 2009).…”
Section: Loss Of Rb Function and Chromosomal Instability (Cin)mentioning
confidence: 99%